Analisis Kesulitan Belajar Pada Materi Menulis Karangan Dintinjau Dari Kepercayaan Diri siswa kelas IV SDN 23 Singkawang - Rahmawati, Elvi; Marhayani, Dina Anika; Wijaya, Andika Kusuma (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: The objectives of this research are (1) to describe the learning difficulties of students in terms of self-confidence in the subject of writing compositions in the fourth-grade curriculum; (2) to describe the factors contributing to learning difficulties in writing compositions among fourth-grade students. This research employs a qualitative descriptive method. The subjects of the study are students from class IV A at SDN 23 Singkawang. Data collection techniques in this research include tests, non-tests, and interviews. The data analysis technique used is the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that (1) learning difficulties in writing compositions, viewed from the perspective of student self-confidence, are as follows: (a) students with high self-confidence, some have been able to perform the indicators well, with an average score of 60 in the medium category; (b) students with medium self-confidence mostly experience difficulties in learning to write compositions, with an average self-confidence level of 41.6 in the low category; (c) students with low self-confidence experience learning difficulties, with an average score of 27.5 in the low category. (2) Factors influencing learning difficulties in writing compositions are (a) internal factors, including low learning outcomes and difficulty in composing sentences, mismatch between effort and results, attitudes during learning, and emotional symptoms; (b) external factors, including delays in completing assignments and deviant behavior during learning. Based on the analysis of learning difficulties in writing compositions from the perspective of self-confidence, it can be concluded that students experience significant learning difficulties, as evidenced by an average score of 35, falling into the low category, with 25 out of 28 students being in the low category.Keywords: Learning difficulties, Writing compositions, Self-confidence Abstrak: Tujuan penelitian ini adalah (1) untuk mendeskripsikan kesulitan belajar siswa ditinjau dari kepercayaan diri pada materi menulis karangan materi kelas IV; (2) untuk mendeskripsikan faktor kesulitan belajar pada materi menulis karangan siswa kelas IV. Metode penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah siswa kelas IV A SDN 23 Singkawang. Teknik pengumpulan data dalam penelitian ini menggunakan  tes, non tes Dan wawancara . Teknik analisis data yang digunakan yaitu model Miles dan Huberman yang terdiri dari reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian menunjukan bahwa, (1) kesulitan belajar menulis karangan yang ditinjau dari kepercayaan diri siswa yaitu (a) siswa dengan kepercayaan diri dengan kategori tinggi ada sebagian sudah mampu melaksanakan indikator dengan baik dan mempunyai rata-rata 60 dengan kriteria sedang (b) siswa dengan kepercayan diri  sedang hampir semua  mengalami kesulitan pada pembelajaran menulis karangan dan mempunyai tingkat kepercayaan diri dengan rata – rata 41,6 dengan kriteria Rendah (c) siswa dengan kepercayaan diri rendah mengalami kesulitan belajar dengan rata-rata 27,5 dengan kriteria rendah; (2) faktor yang mempengaruhi kesulitan belajar pada materi menulis karangan yaitu (a) faktor internal yaitu rendahnya hasil belajar siswa dan kesulitan menyusun kalimat, ketidaksesuaian usaha dan hasil, sikap selama pembelajaran dan gejala emosional,  (b) faktor eksternal yaitu keterlambatan dalam mengerjakan tugas, dan perilaku menyimpang selama pembelajaran. Berdasarkan hasil analisis kesulitan belajar menulis karangan siswa ditinjau dari kepercayaan diri dapat disimpulkan bahwa kesulitan belajar siswa mengalami kesulitan yang signifikan dilihat dari nilai rata – rata 35 berada pada kriteria rendah dengan jumlah siswa 25 dari 28 siswa berada kriteria rendah.Kata Kunci: Kesulitan Belajar, Menulis Karangan, Kepercayaan Diri